Investigating the Status of Physical Activity, Adherence to Treatment, and Quality of Life in Individuals with Asthma - Soheila Rabie Siahkali; Mojghan Sadat Aghvamy; Mohammad Javad Naghihoo (Preventive Care in Nursing and Midwifery Journal)
Background: Adherence to treatment and regular physical activity in individuals with asthma will culminate in favorable clinical outcomes, including an effective disease management and an improved quality of life. Objectives: The present study aimed to determine the physical activity level and association with adherence to treatment and quality of life in individuals with asthma. Methods: This cross-sectional study was conducted on 505 individuals referring to the respiratory ward of Vali-e-Asr Hospital in Zanjan, Iran. Participants were selected using a convenience sampling method. Data were collected using the socio-demographic information form, the International Physical Activity Questionnaires (IPAQ), Modanloo Adherence to Treatment Questionnaire (MATQ), and the St. George's Respiratory Questionnaire (SGRQ). Data analysis was performed using descriptive statistics and the Kruskal-Wallis test in SPSS software version 16. Results: The majority of participants were male (57.2%) with a mean (standard deviation [SD]) age of 66.35 (15.33) years. The physical activity level of the majority of participants was vigorous (43.4%). The mean (SD) total scores for adherence to treatment and quality of life were 120.83 (8.92) and 35.42 (5.02), respectively. According to the findings, physical activity had no statistically significant association with adherence to treatment (p=0.535) and quality of life (p=0.173). Conclusion: In the present study, physical activity level was vigorous in asthmatic participants. Adherence to treatment among participants was at a good level, and quality of life was at a moderate level. Therefore, the design of supportive educational interventions is recommended to improve quality of life and promote lifestyle modification in individuals with asthma.